The post-conflict environment : investigation and critique - Monk, Daniel Bertrand, 1960-; Mundy, Jacob (Knowledge Unlatched Select 2017 (on order), 2014)
In case studies focusing on contemporary crises spanning Africa, the Middle East, and Eastern Europe, the scholars in this volume examine the dominant prescriptive practices of late neoliberal post-conflict interventions--such as statebuilding, peacebuilding, transitional justice, refugee management, reconstruction, and redevelopment--and contend that the post-conflict environment is in fact created and sustained by this international technocratic paradigm of peacebuilding. Key international stakeholders--from activists to politicians, humanitarian agencies to financial institutions--characterize disparate sites as "weak," "fragile," or "failed" states and, as a result, prescribe peacebuilding techniques that paradoxically disable effective management of post-conflict spaces while perpetuating neoliberal political and economic conditions